2006
DOI: 10.1073/pnas.0602132103
|View full text |Cite
|
Sign up to set email alerts
|

Inner-sphere two-electron reduction leads to cleavage and functionalization of coordinated dinitrogen

Abstract: Activation of molecular nitrogen by transition metal complexes is an area of current interest as investigations using the inert N 2 molecule to produce higher-value organonitrogen compounds intensify. In an attempt to extend the addition of hydride reagents E-H (where E ‫؍‬ BR 2, AlR2, and SiR3) to the dinitrogen complex

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
55
1

Year Published

2007
2007
2019
2019

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 61 publications
(57 citation statements)
references
References 55 publications
1
55
1
Order By: Relevance
“…Unfortunately, this potential catalytic cycle was not realized, but in the process of this investigation, the extraordinary reactivity of 13.3 with E-H reagents was revealed. For example, we have reported that 13.3 is capable of undergoing hydroboration [68,69], hydroalumination [70], hydrosilylation [71][72][73] and zirconocene insertion [74] reactions, all of which result in new nitrogen-element (N-E) bond formation [44,67]. An overview of the reactivity of 13.3 towards these reagents is illustrated in Scheme 14.…”
Section: Tantalummentioning
confidence: 97%
“…Unfortunately, this potential catalytic cycle was not realized, but in the process of this investigation, the extraordinary reactivity of 13.3 with E-H reagents was revealed. For example, we have reported that 13.3 is capable of undergoing hydroboration [68,69], hydroalumination [70], hydrosilylation [71][72][73] and zirconocene insertion [74] reactions, all of which result in new nitrogen-element (N-E) bond formation [44,67]. An overview of the reactivity of 13.3 towards these reagents is illustrated in Scheme 14.…”
Section: Tantalummentioning
confidence: 97%
“…Reduction of 7 and elimination of ammonia (N-N cleavage) is exergonic in nature (-11.87 kcal/mol) which is a similar situation to that calculated for the Schrock system. [16] Protonation of [Ru(NH 3 ) 5 (13) is exergonic (-19.2 kcal/mol). In 13, replacement of ammonia by dinitrogen to yield 1 is more endergonic.…”
Section: Resultsmentioning
confidence: 99%
“…[1][2][3][4] In this regard, synthesis and reactivity studies of dinitrogen complexes have become more important. [5] Until Allen and Senoff synthesized the first water soluble dinitrogen complex, [Ru(NH 3 ) 5 N 2 ] 2+ (1), in 1965, dinitrogen was believed to be an inert molecule. [6] In 1968 Taube et al reported a dinuclear Ru II -dinitrogen complex in which dinitrogen bridges two Ru II centers in a head-on fashion.…”
Section: Introductionmentioning
confidence: 99%
“…Related to this, the understanding of the nature of bonding of Ln-N multiple bonds is of fundamental interest and the isolation of terminal imido (Ln=NR) complexes has only recently been reported [162][163][164]. It is also significant to consider the reactivity of Ln-N2 complexes in the context of other low electron count early transition metal complexes; here, N2 cleavage or functionalisation can be achieved through ligand induced reductive cleavage [165][166][167][168][169][170][171][172][173], and more generally, N-N bond scission of reduced N2 derivatives can be attained through metal-ligand cooperativity [174,175].…”
Section: Discussionmentioning
confidence: 99%